A pilot investigation of food insecurity among children seen in an outpatient pediatric nephrology clinic - Starr, Michelle C. (Prev Med Rep, 2018)
Food insecurity (FI) is common - affecting one in six American households with children. FI is defined as limited or uncertain availability of nutritionally adequate and safe foods. Awareness of food insecurity and its impact on health has increased since the American Academy of Pediatrics 2015 policy statement, “Promoting Food Security for All Children.” Though FI is frequently addressed in general pediatric primary care, it is not routinely identified in patients with chronic medical problems. Patients with complex care needs, prescription medication, or restrictive nutritional requirements may be at higher risk of food insecurity. The prevalence of FI in patients with chronic disease, including pediatric patients with kidney disease, remains unknown. We sought to determine the prevalence of FI among our pediatric nephrology clinic patients with a cross-sectional screening pilot study. Nearly 35% of 118 children seen in our pediatric nephrology outpatient clinic lived in food insecure households, a prevalence rate more than double the general pediatric population (16%). Barriers to food security were variable; common themes included challenges with restricted diet and available food, identifying and accessing community resources, and not qualifying for support. For physicians, dietitians, and other health providers that counsel patients with kidney disease on dietary interventions, it is important to be aware of food security status. To our knowledge, this is the first study to assess the prevalence of food insecurity in pediatric patients with kidney disease. Further studies of food insecurity and social determinants of heath in this patient population are needed.